2019
DOI: 10.7554/elife.50047
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of zebrafish melanocyte development by ligand-dependent BMP signaling

Abstract: Preventing terminal differentiation is important in the development and progression of many cancers including melanoma. Recent identification of the BMP ligand GDF6 as a novel melanoma oncogene showed GDF6-activated BMP signaling suppresses differentiation of melanoma cells. Previous studies have identified roles for GDF6 orthologs during early embryonic and neural crest development, but have not identified direct regulation of melanocyte development by GDF6. Here, we investigate the BMP ligand gdf6a, a zebraf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 83 publications
1
21
0
Order By: Relevance
“…The effects of Bmp inhibition appeared to be specific to the ventral fin fold, since the morphology of other organs remained unaltered including the pectoral fins, with a notable exception of the melanophores ( Figure 1G and Supplementary Figures 2A-G). The number of melanophores, which has shown to be negatively regulated by Bmp signaling (Gramann et al, 2019), was concomitantly increased in DMH1-treated embryos (Supplementary Figures 2D,E). Taken together, our data suggest that Bmp signaling selectively restricts the extension of the ventral fin fold along the proximodistal axis in a stage-dependent manner.…”
Section: Bmp Signaling Limits Outgrowth Of the Ventral Fin Foldmentioning
confidence: 86%
“…The effects of Bmp inhibition appeared to be specific to the ventral fin fold, since the morphology of other organs remained unaltered including the pectoral fins, with a notable exception of the melanophores ( Figure 1G and Supplementary Figures 2A-G). The number of melanophores, which has shown to be negatively regulated by Bmp signaling (Gramann et al, 2019), was concomitantly increased in DMH1-treated embryos (Supplementary Figures 2D,E). Taken together, our data suggest that Bmp signaling selectively restricts the extension of the ventral fin fold along the proximodistal axis in a stage-dependent manner.…”
Section: Bmp Signaling Limits Outgrowth Of the Ventral Fin Foldmentioning
confidence: 86%
“…Mechanisms for specifying melanoblast from neural crest cells that involve upregulation of the microphthalmia transcription factor, Mitf ( mitfa in zebrafish) in neural crest cells are conserved in mice, chick and zebrafish [ 30 , 31 ]. Transcription factor Sox10 is required for the expression of mitf in neural crest cells.…”
Section: Discussionmentioning
confidence: 99%
“…When melanoblasts are specified, Mitf transcriptionally activates additional melanocytes differentiation and migration genes, including the melanin synthesis enzymes, dct, tyr, and trp1, and the melanocytes migration and survival gene, kit. Other signaling such as WNT and BMP are also involved in the melanocytes development [ 31 , 32 ]. Therefore, the effect on the cell fate determination of melanogenic lineage induced by 5-HT during embryonic stage and regeneration condition is what we want to illustrate in this research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to insights gained by studying the tumor microenvironment, studies of melanocyte development can inform mechanisms that may be involved in melanoma pathogenesis. Complementing the discovery that GDF6-activated BMP signaling suppresses differentiation to promote invasive melanoma, Gramann and colleagues found that loss of the zebrafish ortholog gdf6a in development leads to an excess of melanocytes specified from the neural crest [112]. Similarly, Lister and colleagues demonstrated that MITF levels, which they directly controlled with the temperature-sensitive hypomorphic mitfa(vc7) allele, are critical to melanocyte development and regeneration in addition to the role in melanoma described above [45].…”
Section: Understanding the Role Of Developmental Mechanisms In Melanomentioning
confidence: 97%